Vitamin D Status Among Children With Juvenile Idiopathic Arthritis: A Multicenter Prospective, Non-randomized, Comparative Study - Kondratyeva, Elena I.; Odinaeva, Nuriniso D.; Klimov, Leonid Ya; Podchernyaeva, Nadeshda S.; Ilenkova, Natalya I.; Dolbnya, Svetlana V.; Zhekaite, Elena K.; Kuryaninova, Victoria A.; Kotova, Yuliya V.; Tikhaya, Margarita I.; Shitkovskaya, Elena P.; Bychina, Liubov V.; et al. (Frontiers in Pediatrics, 2022)
Background Juvenile idiopathic arthritis (JIA) is a chronic autoimmune disease characterized by destructive and inflammatory damage to the joints. The aim in this study was to compare vitamin D levels between children and adolescents, 1–18 years of age, with juvenile idiopathic arthritis (JIA) and a health control group of peers. We considered effects of endogenous, exogenous, and genetic factors on measured differences in vitamin D levels among children with JIA. Methods Our findings are based on a study sample of 150 patients with various variants of JIA and 277 healthy children. The blood level of vitamin D was assessed by calcidiol level. The following factors were included in our analysis: age and sex; level of insolation in three regions of country (center, south, north); assessment of dietary intake of vitamin D; effect of prophylactic doses of cholecalciferol; a relationship between the TaqI, FokI, and BsmI polymorphisms of the VDR gene and serum 25(OH)D concentration. Results We identified a high frequency of low vitamin D among children with JIA, prevalence of 66%, with the medial level of vitamin D being within the range of “insufficient” vitamin D. We also show that the dietary intake of vitamin D by children with JIA is well below expected norms, and that prophylactic doses of vitamin D supplementation (cholecalciferol) at a dose of 500–1,000 IU/day and 1,500–2,000 IU/day do not meet the vitamin D needs of children with JIA. Of importance, we show that vitamin D levels among children with JIA are not affected by clinical therapies to manage the disease nor by the present of VDR genetic variants. Conclusion Prophylactic administration of cholecalciferol and season of year play a determining role in the development of vitamin D deficiency and insufficiency.